IPhone : the missing manual - Pogue, David, 1963- (Missing manual., 2014)
With the iOS 8.1 software and the new iPhone 6 and 6 Plus, Apple has taken its flagship products into new realms of power and beauty. The modern iPhone comes with everything-camera, music player, Internet, flashlight-except a printed manual. Fortunately, David Pogue is back with this expanded edition of his witty, full-color guide: the world's most popular iPhone book. The iPhone 6 and 6 Plus. This book unearths all the secrets of the newest iPhones. Bigger screens, faster chips, astonishing cameras, WiFi calling, Apple Pay, crazy thin.The iOS 8.1 software. Older iPhone models gain predictiv.